Tunable dielectric properties induced by optical fields in barium strontium titanate/manganite heterostructures. (February 2016) - Jin, K.X.; Yang, B.; Zhang, Y.; Luo, B.C.; Chen, L.Y.; Chen, C.L.
Abstract: We systematically investigated the microstructure, leakage current, and tunability of dielectric constants in barium strontium titanate/manganite heterostructures induced by optical fields. It is interesting to note that the values of the relative variation in the dielectric constants have a transition from positive to negative at 150 K when the heterostructure is irradiated by the optical field. This might be attributed to the effect of photogenerated carriers at different structural phases of the barium strontium titanate. These results provide a further understanding of the optical-electric coupling effect and potential applications for tunable microelectronic devices. Graphical abstract: